EFFECTS OF GOVERNMENT FISCAL DEFICITS ON MONEY SUPPLY IN NIGERIA IN BETWEEN 1970 – 2014 - Emmanuel , Umeora Chinweobo; Jackson, Ikeora Emeka (International Journal For Research In Business, Management And Accounting, 2016)
This study investigates the effects of government fiscal deficits on money supply in Nigeria. Because effect of money supply on inflation is almost always inseparable, effect on inflation has also been brought in. Data for the study are secondary data set for 1970 – 2014 obtained from CBN Statistical Bulletin. The method of analysis is Error Correction Model (ECM) and Pairwise Granger Causality. The regression results show that government fiscal deficits have significant and negative effect on money supply and that inflation does not contribute significantly to money supply and fiscal deficits. Pairwise Granger Causality is that money supply granger cause fiscal deficits. The study recommends that government should fiscal deficits so as to control the level of money supply and subsequently inflation.